2022
DOI: 10.3389/fmicb.2021.824229
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Fermentation Products, Residual Non-structural Carbohydrates, and Bacterial Communities of Wilted and Non-wilted Alfalfa Silage With and Without Lactobacillus plantarum Inoculation

Abstract: The aim of this study was to investigate effects of wilting and Lactobacillus plantarum inoculation on the dynamics of the fermentation products, residual non-structural carbohydrates, and bacterial communities in alfalfa silage. Fresh and wilted alfalfa were ensiled with and without L. plantarum for 10, 30, 60, and 90 days. A high-throughput sequencing method for absolute quantification of 16S rRNA was adopted to determine the bacterial community composition at different ensiling periods. For the wilted silag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
(62 reference statements)
1
9
0
Order By: Relevance
“…Hafnia is a gram-negative genus of the family Enterobacteriaceae , which able to grow under anaerobic conditions as well as low pH environments ( Wang et al, 2021 ). As undesirable bacteria, they compete with lactic acid bacteria for nutrients in both anaerobic and aerobic fermentation, resulting in large nutritional loss ( Yang et al, 2021 ). In addition, some species of Hafnia such as Hafnia alvei could transform nitrogen from protein in silages into NH 3 ( Yang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hafnia is a gram-negative genus of the family Enterobacteriaceae , which able to grow under anaerobic conditions as well as low pH environments ( Wang et al, 2021 ). As undesirable bacteria, they compete with lactic acid bacteria for nutrients in both anaerobic and aerobic fermentation, resulting in large nutritional loss ( Yang et al, 2021 ). In addition, some species of Hafnia such as Hafnia alvei could transform nitrogen from protein in silages into NH 3 ( Yang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As undesirable bacteria, they compete with lactic acid bacteria for nutrients in both anaerobic and aerobic fermentation, resulting in large nutritional loss ( Yang et al, 2021 ). In addition, some species of Hafnia such as Hafnia alvei could transform nitrogen from protein in silages into NH 3 ( Yang et al, 2021 ). Hence, the higher relative abundance of Hafnia alvei in CK groups, especially in aerobic exposure, could explain their higher DM loss and NH 3 -N.…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput sequencing has been widely used in recent years to illustrate the microbial community structure in the alfalfa ensiling process ( Guo et al, 2018 ; Yang et al, 2020 , 2022 ), and research in this area has primarily focused on the microbial communities in alfalfa silage. Microbial communities are influenced by many factors such as additives ( Yang et al, 2020 ), moisture content ( Yang et al, 2022 ), and silage density ( Sun et al, 2021 ). The dominant genera changed with the different inoculated lactic acid bacteria (LAB) additives ( Ogunade et al, 2018 ; Fan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Only limited research has focused on the microbial communities of wilted alfalfa (W). Previous studies have indicated that wilting may affect the abundance of epiphytic microbes ( Agarussi et al, 2019a ), and that wilting inhibited the growth of spoilage microorganisms in the early stage of ensiling, which resulting in good fermentation quality ( Yang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation